Keratinase improves the growth performance, meat quality and redox status of broiler chickens fed a diet containing feather meal - Kai-Lin Xu; Guo-Xin Gong; Miao Liu; Lu Yang; Ze-Jing Xu; Si Gao; Meng-Yi Xiao; Tao Ren; Bing-Ji Zhao; Mahmoud M. Khalil; Ling Zhao; Lv-Hui Sun (Poultry Science, 2022)
ABSTRACT: The objective of this study was to assess the effects of dietary supplementation of keratinase on the production of broilers fed a diet containing feather meal. A total of 162 1-d-old Cobb 500 male broiler (n = 9 cages/diet with 6 chicks/cage) were randomly allocated to 3 dietary treatments. The broilers were fed a corn-soybean-feather meal based diet (BD), or BD supplemented with keratinase at 100,000 or 200,000 U/kg for 6 weeks. Compared to the control, dietary supplementation with 200,000 U/kg keratinase increased (P < 0.05) body weight gain (3.6–4.3%) and reduced feed conversion ratio (2.4–5.6%) during the various experimental periods, and also improved (P < 0.05) apparent total tract digestibility of ash and calcium by 45.0% and 8.8%, respectively. Meanwhile, dietary supplementation of keratinase at 100,000 U/kg reduced (P < 0.05) the drip loss (29.2%), while 200,000 U/kg keratinase supplementation increased (P < 0.05) the pH value (1.6%) at 45 min and decreased (P < 0.05) the lightness (L* value; 13.6%) and drip loss (22.1%) of pectoral muscle. Moreover, dietary supplementation of keratinase at both levels of 100,000 and 200,000 U/kg increased (P < 0.05) Glutathione peroxidase activity (82.5–87.5%) and decreased the Malondialdehyde concentration (14.5–18.3%) in the pectoral muscle. In conclusion, dietary supplementation of keratinase at 200,000 U/kg can improve the performance, meat quality, apparent total tract digestibility of nutrients, and redox status of broiler chickens fed a diet containing feather meal.